Development of E-Culture Framework for Ethnic West Papua Using Soft Systems Methodology (SSM) (Journal of Pharmaceutical Negative Results, 2022)
West Papua is a province located in the eastern region of Indonesia and is a division of the Papua Province. The diversity of cultures and ethnicities in the West Papua region is an aspect that needs to be protected due to the influence of the times. The threat of cultural extinction in West Papua is a problem that needs to be resolved at this time. The purpose of this study is to identify and model plans for cultural preservation in the West Papua region. This study aims to build a framework for developing an e-Culture Ethnic West Papua system using the Soft System Methodology (SSM) to produce a model of cultural preservation. Data collection techniques by conducting observations and interviews with related parties. The conceptual model produced in this study can broaden the perspective with a world view so that all levels in society and all existing organizations are involved in preserving the existing culture.